Pengaruh Pemberian Obat Psikotropika terhadap Perilaku Swimming dan Floating pada Mencit (mus musculus) dalam Forced Swimming Test - Haryanto Haryanto; Febriyanti Aswinda; Safira Nur Amalia; Rizka Salzabila J; Fitri Fitri; Muh. Rifkyansyah; Musdalifa Musdalifa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the use of psychotropic substances, which affect the central nervous system and can alter mental functions, behavior, and individual perception. In the medical context, psychotropics have been widely utilized for treating mental disorders such as depression, anxiety, and schizophrenia. The research emphasizes the importance of understanding the mechanisms of psychotropics to optimize their therapeutic benefits while minimizing the risk of adverse effects. The study employed animal models, specifically rats, using the forced swimming test (FST) to assess the antidepressant and sedative effects of various substances, including Esilgan, Xanax, Zolmia, Syzygium malaccense leaf extract, and lelap (herbal), with NaCMC as a negative control. The results demonstrated varying sedative and antidepressant effects among the substances, with Xanax exhibiting the most significant antidepressant effect, while Syzygium malaccense leaf extract showed potential as a natural sedative agent. The study also underscores the importance of applying the 3R ethical principles (Replacement, Reduction, Refinement) in animal research and highlights the need for alternative methods to reduce reliance on animal testing. These findings are expected to serve as a foundation for developing safer, more effective, and ethical psychotropic therapies for mental disorders in the future.